2009
DOI: 10.1542/peds.2008-0477
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Behavior Is Associated With the Early Neurobehavioral Development of Very Preterm Children

Abstract: Specific parenting behaviors, particularly parent-child synchrony, were associated with neurobehavioral development. These findings have implications for the development of targeted parent-based interventions to promote positive outcomes across different developmental domains during the first 2 years of life for very preterm children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
172
4
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(186 citation statements)
references
References 43 publications
3
172
4
7
Order By: Relevance
“…In relation to social and personal development studies, the reviewed studies found that preterm children have problems in social adjustment in the first months (35,68), in task persistence also at 4 years (35,44), in emotional regulation and social interactions from the first year of life (37,39,44,68,71), in emotional adjustment (48,68), in the development of secure attachment and social competence in the early years (5,48,71), in internalizing behavior at two years (such as shyness, fear, anxiety, depression) (5, 71) and behavioral difficulties, such as hyperactivity at 3, 5 and 6 years (76). However, there is no agreement between the studies regarding externalizing behavior problems, such as aggression, hyperactivity and defiance, or emotional expression and regulation difficulties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In relation to social and personal development studies, the reviewed studies found that preterm children have problems in social adjustment in the first months (35,68), in task persistence also at 4 years (35,44), in emotional regulation and social interactions from the first year of life (37,39,44,68,71), in emotional adjustment (48,68), in the development of secure attachment and social competence in the early years (5,48,71), in internalizing behavior at two years (such as shyness, fear, anxiety, depression) (5, 71) and behavioral difficulties, such as hyperactivity at 3, 5 and 6 years (76). However, there is no agreement between the studies regarding externalizing behavior problems, such as aggression, hyperactivity and defiance, or emotional expression and regulation difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no agreement between the studies regarding externalizing behavior problems, such as aggression, hyperactivity and defiance, or emotional expression and regulation difficulties. Some studies suggest that preterm children have these difficulties (5,36,48,71), while other studies suggest that preterm children have no problems with temperament at 12 months (69), in adaptive behavior and in self-control at 2 and 5-6 years (36), in effective problem solving with parents (44), or in externalizing behavior at two years (5). They also do not seem to present temperamental syndrome at five years, when children are most emotional, social and patient, less directive and reactive to frustration (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, interactions characterized by caregiver sensitivity and synchronized dyadic interactions correlate with better developmental outcomes for preterm infants (Forcada-Guex, Pierrehumbert, Borghini, Moessinger, & Muller-Nix, 2006;Treyvaud, et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The idea that parents have an impact on their child's development is well known (Treyvaud, Anderson, & Howard, et al, 2009;Guajardo, Snyder & Petersen, 2009). …”
Section: Parents and Children Influence Play Relationshipsmentioning
confidence: 99%